Effects of an upper body conditioning stimulus on lower body post-activation potentiation - Laskin, G. (Southern Connecticut State University, 2020)
One strategy to improve strength and power development in athletes is by implementing complex training, where both high-loadand plyometric movements are alternated one after the other throughout a workout. Research suggests that when a high-load, low-velocity conditioning stimulus (CS) is performed just prior to a biomechanically similar plyometric movement, the performance of the plyometric movement is acutely enhancedin a phenomenon called post-activation potentiation (PAP). Despite the positive influence PAP can have on power production, research has only investigated the existence of PAP when comparing biomechanically similar movements. PURPOSE:To determine if an upper bodyCS can elicit a PAP response in a lower body plyometric exercise and to investigate the optimal time course for PAP between an upper body CS and lower body plyometric exercise. METHODS: Eight (8) resistance-trained males (23.5 ± 2.7y; 177.5± 3.2cm; 81.7± 5.8 kg) participated in the study. Participants performed one set of three countermovement jumps (CMJs) before (pre-CS) and three sets of three CMJs after (post-CS) an upper body CS. Muscle activation in the vastus lateralis, gastrocnemius, and gluteus maximus were compared between pre-CS andthe threepost-CS conditionsusing surface electromyography. Changes in jump height, work, power output, and rate of force development (RFD) during the early and late stages of the CMJ take-off between the conditions were analyzed using a force plate. A repeated-measures MANOVA with LSD post-hoc testing was used to determine differences using SPSS. The level of significance was set at p<.10. RESULTS: There were no significant differences in muscle activation for any of the muscles measured, jump height, work, or the early stage of RFD (p<.10). There was a significant decrease in power output between pre-CS and the final set of jumps post-CS (p=.057). There was a significant increase in the late stage of RFD between pre-CS and the final set of jumps post-CS (p=.01).CONCLUSIONS: The results of the study suggest that an upper body CS may not be a useful tool to influence PAP in the lower body.Performing an upper body strength exercise complexed with a lower body plyometric does not seem to have disadvantages, and could still be a useful strategy to maximize workout efficiency and organizationas long as proper fatigue management is incorporated. Strength coaches desiring to use an upper-lower complex should individualize volume, intensity, and rest periods forthe athlete to optimize the relationship between workout efficiency and acute fatigue.